Perbedaan Rasio Profitabilitas Bank di Indonesia sebelum dan saat Pandemi Covid-19 - Amrina, Dania Hellin; Faizah, Iva; Supriyaningsih, Okta (Al-Mashrof: Islamic Banking and Finance, 2021)
This study aims to analyze differences in the financial performance of banks in Indonesia using the profitability ratios of Return on Assets (ROA) and Net Interest Margin (NIM). The method used in this study used a different paired sample t-test. The results of research on the financial performance of banks in Indonesia using the ROA and NIM ratios show differences in banks' financial performance before and during the covid-19 pandemic. Statistical results show a decline in banks' financial performance in Indonesia before and during the COVID-19 pandemic. The decline in financial performance during the pandemic is inevitable, not only from the banking sector. Indonesian banks are not yet effective enough in using assets to generate profits during the pandemic, and weak credit growth so that the allocation of third party funds are placed more in State Securities (SBN) is one of the causes.Keywords: Profitability Ratio, ROA, NIM, Covid-19